MENINGKATKAN KETERAMPILAN MEMBUAT KERIPIK KENTANG MELALUI METODE LATIHAN BAGI ANAK TUNARUNGU - Aspuriyah Aspuriyah; Kasiyati Kasiyati; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2013)
This study aimed to: 1) Determine the implementation process in improving skills to make potato chips through training methods and 2) prove that the method of exercises can improve the skills of making potato chips in deaf children class V SDLB 20 Nanbalimo Solok City.This study removed using action research method (Classroom Action Research) conducted in collaboration with colleagues. Data were collected through observation and testing techniques, and then analyzed qualitatively and quantitatively. The results showed that 1) the implementation process in improving skills to make potato chips through training methods done in two cycles. Cycle I conducted five meetings with the goal of cycle "so that children are able to recognize and process the material for making potato chips." While the second cycle followed by "frying potato chips" conducted in four sessions. Activities carried out by following the flow of the cycle: planning, implementation, observation and reflection. 2) The results of the study proved that the child's children's ability to make potato chips with current training methods of increased. It proved: results asessmen Learning outcomes: children's ability to make potato chips with current training methods of assessment are: IN is (43.3%), while SC only (36.7%). After being given a lesson in the first cycle with training methods and cognitive ability for making potato chips IN is (86,7%) and SC was (80%). Cycle II results obtained IN (100%) and (93,3%) have been able to perform independently. It can be concluded that the method of exercises can improve the skills of making potato chips in deaf children class V SDLB 20 Nanbalimo Solok City. Keterampilaan suggested to teachers to use teaching methods in practice other skills.